Building women's climate resilience: AICCRA Ghana VSLA plus intervention - Odomma, Faustina Obeng; Kyere, Reginald Ofori; Dalaa, Mustapha Alasan; Tepa-Yotto, Ghislain (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Supporting women’s groups and their collective action is considered as one of the key ways to increase their climate resilience. Women’s groups are a means to reach women with capacity building activities, and also serve as a platform where they exercise collective and individual agency to take adaptive decisions. Strengthening the capacity of women’s groups on climate information services (CIS) and climate smart agriculture (CSA) innovations is a key pillar for gender-responsive climate smart agriculture intervention. In this Info Note, we present insights from working with women village savings and loans associations (VSLA) in Ghana to build their individual and collective adaptive capacities through a VSLA plus intervention. Through these VSLAs, women became active in selecting and using CIS-CSA innovations that responded to their lived realities. The novelty of the VSLA plus intervention manifested in the active participation of women through their collective action to co-prioritise, implement and scale validated CIS-CSA innovations that help them to chart the course of their climate resilient futures.